High light transmittance and low floating fiber glass fiber reinforced PC composition and preparation method thereof

By combining modified glass fiber with PC, the problem of floating fiber phenomenon and poor transparency in glass fiber reinforced PC materials is solved, and the effects of high light transmittance and low floating fiber are achieved, which improves the mechanical properties and transparency of the material.

CN116082814BActive Publication Date: 2024-12-24SHANGHAI KUMHO SUNNY PLASTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211572338.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2024-12-24
Estimated Expiration
2042-12-08

AI Technical Summary

Technical Problem

The existing glass fiber reinforced PC materials have problems such as floating fiber phenomenon, low bond strength and poor transparency, which cannot meet the needs of high light transmittance and low floating fiber.

Method used

By combining the modified glass fibers with PCs in the polymerization process of aromatic dihydroxy compound, the modified glass fiber masterbatches are formed, which improves the compatibility and dispersion of glass fibers with PCs, reduces the floating fiber phenomenon, and uses ultrasound and catalysts. Use optimized reaction conditions to improve the transparency and mechanical properties of the material.

Benefits of technology

A glass fiber reinforced PC material with high light transmittance and low floating fiber is achieved, which significantly improves the bending strength, tensile strength and impact strength of the material, while maintaining good transparency and dimensional stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003988611890000101
    Figure BDA0003988611890000101
  • Figure BDA0003988611890000111
    Figure BDA0003988611890000111
Patent Text Reader

Abstract

The present invention discloses a high-transmittance low-floating fiber glass fiber reinforced PC composition and a preparation method thereof; the composition comprises: 40-70 parts of PC resin, 30-60 parts of glass fiber masterbatch, and 0.1-1 parts of antioxidant; the glass fiber masterbatch is obtained by modifying the surface of glass fiber and grafting aromatic dihydroxy compounds onto the modified glass fiber, and then adding the modified glass fiber during the PC polymerization process to obtain the modified glass fiber masterbatch. Compared with directly adding glass fiber to PC resin, the present invention can enhance the compatibility of glass fiber and PC after grafting PC segments on the surface of glass fiber, improve its dispersion in PC and reduce surface floating fibers, has good light transmittance and low surface floating fiber effects, and at the same time, the bending strength, tensile strength and impact strength of the material are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and relates to a glass fiber reinforced polycarbonate composition, and in particular to a high-transmittance and low-floating fiber glass fiber reinforced PC composition and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) has good heat resistance, impact resistance, glossiness, and transparency, and is an important engineering plastic. Glass fiber has the characteristics of high mechanical strength, good insulation, strong heat resistance, and good corrosion resistance. It is an excellent inorganic non-metallic material and is widely used in plastic filling and modification. After glass fiber reinforced PC, the heat resistance of PC resin is retained, and the rigidity of PC is significantly improved. The linear expansion coefficient is significantly reduced, the dimensional stability is greatly improved, and the mold shrinkage rate is reduced. It overcomes the problem of PC's lack of fatigue strength and stress cracking, making it suitable for fields with high mechanical performance requirements. It is an ideal material for automotive interior and exterior trims, home appliance housings, and electronic communication device housings.

[0003] However, when existing glass fiber materials are used to reinforce PC, the following problems are prone to occur: 1. Glass fiber is easy to float on the surface during the flow of plastic melt filling the mold, resulting in floating fiber phenomenon, and the appearance of the product is not good; 2. The polarity difference between PC and glass fiber is large, and the compatibility is poor. The bonding strength of the two-phase interface of glass fiber reinforced PC material is low, and the material performance is poor, which limits the use of the material; 3. When glass fiber modifies PC, it will affect the transparency of PC, and the light transmittance is low, which cannot adapt to new market demands. Therefore, it is necessary to propose a new glass fiber reinforced PC material with high light transmittance and low floating fiber, which can reduce the floating fiber phenomenon and improve the impact strength and light transmittance while ensuring good rigidity and dimensional stability.

[0004] Through searching the existing patent documents, it was found that the Chinese patent document CN112778738A disclosed a high-strength, low-mold-temperature, low-floating-fiber polycarbonate composite material and its preparation method. By using hyperbranched polyimide-modified glass fiber and toughening agent, the tensile strength, bending strength and impact strength of the polycarbonate composite material, and the surface floating fiber phenomenon were improved. However, the hyperbranched polyimide-modified glass fiber of the patent is not compatible with PC, resulting in low bonding strength between the glass fiber and PC, and a toughening agent needs to be added to improve the impact strength. The addition of the toughening agent will cause the transparency of the material to decrease significantly, and the low compatibility leads to poor wettability of the glass fiber in PC, and the effect of improving the floating fiber is limited.

[0005] The Chinese patent document CN111019315B discloses a glass fiber reinforced PC material and its preparation method and use. After the glass fiber is modified by an elastomer, a coupling agent and a rare earth ion, it is added to the PC material with a compatibilizer, thereby improving the dispersion of the glass fiber in the PC matrix material and enhancing the interaction between the glass fiber and the PC matrix material, thereby improving the mechanical properties of the glass fiber reinforced PC material. However, the modification method of the patent will lead to a decrease in the transparency of the material, and the modified glass fiber is not compatible with PC, and the effect of improving the floating fiber is not good.

[0006] The Chinese patent document CN111704792A discloses a high-transmittance glass fiber reinforced PC composite material, which improves the transparency and light transmittance of the composite material by using a highly transparent high-refractive index glass fiber with a refractive index of 1.570 to 1.590. However, the glass fiber in the patent is directly added to the PC resin, which has poor compatibility with PC and poor wettability, and cannot improve the surface floating fiber phenomenon. In addition, the bonding strength with PC is low, which reduces the impact performance of the material. Summary of the invention

[0007] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a high-transmittance and low-floating fiberglass reinforced PC composition and a preparation method thereof.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] The present invention relates to a glass fiber reinforced PC composition, comprising the following components in parts by weight: 40-70 parts of PC, 30-60 parts of glass fiber masterbatch, and 0.1-1 part of antioxidant; the glass fiber masterbatch is prepared by adding an aromatic dihydroxy compound to modify glass fiber during the PC polymerization process. Specifically, the glass fiber surface is modified and grafted with an aromatic dihydroxy compound to obtain a modified glass fiber, and then the modified glass fiber is added during the PC polymerization process to obtain the modified glass fiber masterbatch.

[0010] As an embodiment, PC is a linear homopolymer polycarbonate of bisphenol A, and has a melt index of 10 to 30 g / 10 min at 300° C. and 1.2 kg.

[0011] As an embodiment, the glass fiber has a diameter of 5-20 μm, a length of 1-5 mm, and a refractive index of 1.57.

[0012] As an embodiment, the antioxidant is selected from one or more of aromatic amine antioxidants, hindered phenol antioxidants, phosphite antioxidants, thioester antioxidants, aromatic phosphates, and pentaerythritol esters.

[0013] As an embodiment, the glass fiber masterbatch is prepared by a method comprising the following steps:

[0014] S1. Preparation of modified glass fiber:

[0015] S1-1. Under nitrogen protection, add glass fiber and diphenylmethane diisocyanate to anhydrous toluene, perform ultrasonic treatment for 10-30 min, heat and stir at 70-90° C. for 0.5-4 h, filter and wash with anhydrous toluene, and dry at 40-80° C. to obtain diphenylmethane diisocyanate-modified glass fiber; in some specific implementation examples, filter and wash three times with anhydrous toluene, and dry at 40-80° C. for 3-8 h to obtain diphenylmethane diisocyanate-modified glass fiber;

[0016] S1-2, under nitrogen protection, adding the diphenylmethane diisocyanate modified glass fiber and the aromatic dihydroxy compound to anhydrous toluene, ultrasonicating for 10-30 min, heating and stirring at 60-80° C. for 2-6 h, filtering and washing with anhydrous toluene, and drying at 40-80° C. to obtain the modified glass fiber; in some specific implementation examples, filtering and washing with anhydrous toluene three times, and drying at 40-80° C. for 3-6 h to obtain the modified glass fiber;

[0017] S2. Preparation of modified glass fiber masterbatch:

[0018] An aromatic dihydroxy compound and the modified glass fiber are added to a mixed solvent of water and dichloromethane, and ultrasonic treatment is performed for 10-30 minutes. Phosgene is introduced at a rate of 15-30 g / min, and a 30-50% mass fraction of sodium hydroxide aqueous solution is slowly added dropwise to control the pH value between 8 and 11. The mixture is stirred at 10-40° C. for 1-3 hours. Triethylamine is then added, and the mixture is stirred at 10-40° C. for 1-3 hours. The mixture is filtered and washed with water, and dried at 70-90° C. to obtain a modified glass fiber masterbatch. In some implementation examples, the mixture is filtered and washed with water three times, and dried at 70-90° C. for 4-8 hours to obtain a modified glass fiber masterbatch.

[0019] As an embodiment, in step S1-1, the amount of diphenylmethane diisocyanate added is 1-5g per 100ml of anhydrous toluene. When the amount of diphenylmethane diisocyanate added per 100ml of anhydrous toluene is less than 1g, the concentration of isocyanate is low, the reaction efficiency is low, the reaction time is too long, and the production efficiency is low; when the amount of diphenylmethane diisocyanate is higher than 5g, the amount of glass fiber added later is too much, the dispersion effect of glass fiber in toluene becomes poor, agglomeration occurs easily, and the surface reaction is insufficient.

[0020] As an embodiment, in step S1-1, the amount of glass fiber added is such that the mass ratio of glass fiber to diphenylmethane diisocyanate is 1:0.1-0.5. When the mass ratio of glass fiber to diphenylmethane diisocyanate is lower than 1:0.5, the relative content of isocyanate is higher, the surface modification effect of glass fiber is not significantly increased, and the cost is too high; when the mass ratio of glass fiber to diphenylmethane diisocyanate is higher than 1:0.1, the relative content of isocyanate is lower, resulting in too few -CNO groups on the surface of glass fiber, too little PC amount subsequently grafted onto glass fiber, and poor compatibility between modified glass fiber and PC.

[0021] As an embodiment, in step S1-2, the amount of diphenylmethane diisocyanate modified glass fiber added is 1-5g of the mass of diphenylmethane diisocyanate modified glass fiber added to 100ml of anhydrous toluene. When the amount of diphenylmethane diisocyanate modified glass fiber added to 100ml of anhydrous toluene is less than 1g, the concentration of the modified glass fiber is low, the reaction efficiency is low, the reaction time is too long, and the production efficiency is low; when the amount of diphenylmethane diisocyanate modified glass fiber is higher than 5g, the dispersion effect of the modified glass fiber in toluene becomes poor, it is easy to agglomerate, and the surface reaction is insufficient.

[0022] As an embodiment, in step S1-2, the amount of the aromatic dihydroxy compound added is such that the mass ratio of the aromatic dihydroxy compound to the diphenylmethane diisocyanate-modified glass fiber is 1:0.5-1. When the mass ratio of the aromatic dihydroxy compound to the diphenylmethane diisocyanate-modified glass fiber is lower than 1:1, the relative content of the aromatic dihydroxy compound is low, resulting in a low amount of the aromatic dihydroxy compound grafted on the surface of the glass fiber, and the compatibility of the modified glass fiber and PC is poor; when the mass ratio of the aromatic dihydroxy compound to the diphenylmethane diisocyanate-modified glass fiber is higher than 1:0.5, the relative content of the aromatic dihydroxy compound is high, the surface modification effect of the glass fiber is not significantly increased, and the cost is too high.

[0023] As an embodiment, in steps S1-1, S1-2, and S2, the ultrasound is ultrasonic dispersion.

[0024] As an embodiment, in step S2, the volume ratio of water to dichloromethane in the mixed solvent is 1:2-4. When the volume ratio of water to dichloromethane is lower than 1:4, the relative content of water is lower, resulting in a reduction in the amount of aromatic dihydroxy compound added and a decrease in production efficiency; when the volume ratio of water to dichloromethane is higher than 1:2, the relative content of dichloromethane is lower, resulting in a reduction in the amount of phosgene dissolved and a decrease in production efficiency.

[0025] As an embodiment, in step S2, the amount of the aromatic dihydroxy compound added is 5-25 g per 100 ml of water. If the amount of the aromatic dihydroxy compound added per 100 ml of water is less than 5 g, the concentration is low, the reaction efficiency is low, and the reaction time is too long and the production efficiency is low; if the amount of the aromatic dihydroxy compound is higher than 25 g, the amount of modified glass fiber added later is too much, the dispersion effect in toluene becomes poor, agglomeration is easy to occur, and the surface reaction is insufficient.

[0026] As an embodiment, in step S2, the amount of modified glass fiber added is such that the mass ratio of modified glass fiber to aromatic dihydroxy compound is 1:0.5-4.

[0027] As an embodiment, in step S2, the amount of phosgene added is 100-120 g per 1 mol of the aromatic dihydroxy compound. If the amount of phosgene added per 1 mol of the aromatic dihydroxy compound is less than 100 g, there will be excess aromatic dihydroxy compound that does not participate in the reaction, resulting in a waste of raw materials; if the amount of phosgene added is more than 120 g, the excess phosgene does not participate in the reaction, resulting in an increase in cost.

[0028] As an embodiment, in step S2, the amount of triethylamine added is 1-2 ml per 1 mol of the aromatic dihydroxy compound. If the amount of triethylamine added per 1 mol of the aromatic dihydroxy compound is less than 1 ml, the catalytic effect of triethylamine is not obvious, resulting in low reaction efficiency; if the amount of triethylamine is greater than 2 ml, the effect of improving the reaction efficiency is not obvious, resulting in an increase in cost.

[0029] As an embodiment, examples of the aromatic dihydroxy compound include the following:

[0030] 1,2-dihydroxybenzene, 1,3-dihydroxybenzene, 1,4-dihydroxybenzene, and other dihydroxybenzenes;

[0031] 2,5-dihydroxybiphenyl, 2,2'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl, and other dihydroxybiphenyls;

[0032] 2,2'-dihydroxy-1,1'-binaphthyl, 1,2-dihydroxynaphthalene, 1,3-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 1,7-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, and other dihydroxynaphthalenes;

[0033] 2,2'-dihydroxydiphenyl ether, 3,3'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 1,4-bis(3-hydroxyphenoxy)benzene, 1,3-bis(4-hydroxyphenoxy)benzene, and other dihydroxydiaryl ethers;

[0034] 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A), 1,1-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(3-methoxy-4-hydroxyphenyl)propane, 2-(4-hydroxyphenyl)-2-(3-methoxy-4-hydroxyphenyl)propane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2 ,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 2-(4-hydroxyphenyl)-2-(3-cyclohexyl-4-hydroxyphenyl)propane, α,α'-bis(4-hydroxyphenyl)-1,4-diisopropylbenzene, 1,3-bis[2-(4-hydroxyphenyl)-2-propyl]benzene, bis(4-hydroxyphenyl)methane, bis(4-hydroxyphenyl)cyclohexylmethane, bis(4-hydroxyphenyl)phenylmethane, bis(4-hydroxyphenyl)(4-propenylphenyl)methane , bis(4-hydroxyphenyl)diphenylmethane, bis(4-hydroxyphenyl)naphthylmethane, 1,1-bis(4-hydroxyphenyl)ethane, 1,2-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)-1-naphthylethane, 1,1-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl) bis(hydroxyaryl)alkanes such as bis(hydroxyaryl)alkanes, bis(hydroxyphenyl)hexane, 2,2-bis(4-hydroxyphenyl)hexane, 1,1-bis(4-hydroxyphenyl)octane, 2,2-bis(4-hydroxyphenyl)octane, 1-bis(4-hydroxyphenyl)hexane, 2-bis(4-hydroxyphenyl)hexane, 4,4-bis(4-hydroxyphenyl)heptane, 2,2-bis(4-hydroxyphenyl)nonane, 1,10-bis(4-hydroxyphenyl)decane, 1,1-bis(4-hydroxyphenyl)dodecane, etc.;

[0035] 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,4-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,4-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,5-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4 1,1-bis(4-hydroxyphenyl)-3-propyl-5-methylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3-tert-butylcyclohexane, 1,1-bis(4-hydroxyphenyl)-4-tert-butylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3-phenylcyclohexane, 1,1-bis(4-hydroxyphenyl)-4-phenylcyclohexane, and other bis(hydroxyaryl)cycloalkanes;

[0036] 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, and other bisphenols containing Cardo structure;

[0037] 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxy-3,3'-dimethyl diphenyl sulfide, and other dihydroxy diaryl sulfides;

[0038] 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, and other dihydroxydiaryl sulfoxides;

[0039] 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxy-3,3'-dimethyl diphenyl sulfone, and other dihydroxy diaryl sulfones;

[0040] Among these, bis(hydroxyaryl)alkanes are preferred, bis(4-hydroxyphenyl)alkanes are preferred, and 2,2-bis(4-hydroxyphenyl)propane (ie, bisphenol A) is particularly preferred.

[0041] It should be noted that the aromatic dihydroxy compounds may be used alone or in combination of two or more.

[0042] In order to obtain a branched PC resin, a trifunctional or higher polyfunctional compound (branching agent) may be used as a part of the aromatic dihydroxy compound in an amount of 0.1 to 10 mol %, preferably 0.1 to 3 mol %.

[0043] Examples of the trifunctional or higher polyfunctional compound used in this case include the following:

[0044] 1,3,5-trihydroxybenzene, 4,6-dimethyl-2,4,6-tri(4-hydroxyphenyl)-2-heptene, 4,6-dimethyl-2,4,6-tri(4-hydroxyphenyl)heptane, 2,6-dimethyl-2,4,6-tri(4-hydroxyphenyl)-3-heptene, 1,3,5-tri(4-hydroxyphenyl)benzene, 1,1,1-tri(4-hydroxyphenyl)ethane and other polyhydroxy compounds, or 3,3-bis(4-hydroxyaryl)oxyindole (i.e. indigo bisphenol), 5-chloro indigo bisphenol, 5,7-dichloro indigo bisphenol, 5-bromo indigo bisphenol, etc.

[0045] In addition, the trifunctional or higher polyfunctional compound can be used alone or in combination of two or more.

[0046] The present invention also relates to a method for preparing a glass fiber reinforced PC composition, comprising the following steps: 40-70 parts of PC, 30-60 parts of modified glass fiber masterbatch, and 0.1-1 part of antioxidant are mixed at high speed and placed in a screw machine, the speed of the screw machine is controlled to be 300-500 rpm, the temperature is controlled to be 200-270° C., and extrusion granulation is performed to obtain the glass fiber reinforced PC composition.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The present invention firstly grafts an aromatic dihydroxy compound structure onto the surface of the glass fiber through a series of chemical reactions, thereby providing a reaction site for subsequent in-situ polymerization of PC; specifically, the glass fiber and diphenylmethane diisocyanate are first mixed, and under a suitable addition amount and reaction time, one -CNO group of most diphenylmethane diisocyanate reacts with a hydroxyl group on the surface of the glass fiber, and another -CNO group is retained, and two -CNO groups of a smaller amount of diphenylmethane diisocyanate react with one or two hydroxyl groups on the surface of the glass fiber respectively; after the diphenylmethane diisocyanate-modified glass fiber is mixed with the aromatic dihydroxy compound, the -CNO group on the surface of the glass fiber that has not reacted reacts with the phenolic hydroxyl group of the aromatic dihydroxy compound, so that the aromatic dihydroxy compound is grafted onto the surface, one hydroxyl group in most of the aromatic dihydroxy compounds reacts with the -CNO group, and two hydroxyl groups in a small amount of the aromatic dihydroxy compounds react with the -CNO group.

[0049] Then, during the PC polymerization process, modified glass fibers grafted with aromatic dihydroxy compounds are added to graft PC molecular chains on the surface of the glass fibers, and the glass fibers are anchored in the PC matrix resin to obtain modified glass fiber masterbatch. The aromatic dihydroxy compound groups grafted on the surface of the modified glass fibers and the free aromatic dihydroxy compounds in the solvent first react with sodium hydroxide in water to form a sodium salt structure, and then undergo a polycondensation reaction with phosgene, thereby generating low relative molecular mass PC on the surface of the modified glass fibers and in the solvent. After the addition of triethylamine, the PC chain segments on the surface of the modified glass fibers and in the solvent will undergo an intermolecular polycondensation reaction to generate high relative molecular mass PC.

[0050] Compared with directly adding glass fiber to PC resin, grafting PC segments on the surface of glass fiber can enhance the compatibility of glass fiber and PC, improve its dispersion in PC and reduce surface floating fiber. It has good light transmittance and low surface floating fiber effect. At the same time, the bending strength, tensile strength and impact strength of the material are significantly improved. DETAILED DESCRIPTION

[0051] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0052] The components and characteristics involved in the following examples and comparative examples are as follows:

[0053] PC: Linear homopolymer polycarbonate of bisphenol A, with a melt index of 20 g / 10 min at 300 °C and 1.2 kg;

[0054] Glass fiber: diameter 10μm, length 3mm, refractive index 1.57;

[0055] Aromatic dihydroxy compounds: bisphenol A.

[0056] Example 1

[0057] This embodiment provides a high-transmittance, low-floating fiberglass reinforced PC composition and a preparation method thereof, the method comprising the following steps:

[0058] (1) Preparation of glass fiber grafted with bisphenol A:

[0059] Under nitrogen protection, add 16 g of glass fiber and 4 g of diphenylmethane diisocyanate to 100 ml of anhydrous toluene, act ultrasonically for 30 min, heat and stir at 70 ° C for 2 h, filter and wash three times with anhydrous toluene, and dry at 80 ° C for 4 h to obtain diphenylmethane diisocyanate-modified glass fiber; under nitrogen protection, add 4 g of diphenylmethane diisocyanate-modified glass fiber obtained in the above steps and 4 g of bisphenol A to 100 ml of anhydrous toluene, act ultrasonically for 30 min, heat and stir at 80 ° C for 3 h, filter and wash three times with anhydrous toluene, and dry at 80 ° C for 6 h to obtain modified glass fiber.

[0060] (2) Preparation of modified glass fiber masterbatch:

[0061] 900 g of bisphenol A and 250 g of the modified glass fiber prepared in step (1) were added to a mixed solvent of 4 L of water and 12 L of dichloromethane. Under ultrasonic action for 30 min, 420 g of phosgene was introduced at a rate of 30 g / min, and a 50% by mass aqueous solution of sodium hydroxide was slowly added dropwise to control the pH value at 10.5. The mixture was stirred at 30° C. for 1 h. Then, 5 ml of triethylamine was added, the mixture was stirred at 30° C. for 2 h, filtered and washed with water three times, and dried at 90° C. for 8 h to obtain a modified glass fiber masterbatch.

[0062] (3) Prepare the following components by weight:

[0063] PC 50 copies,

[0064] 50 parts of modified glass fiber masterbatch,

[0065] Antioxidant 1010 0.2 parts;

[0066] The ingredients in step (3) are added into a high-speed mixer, mixed thoroughly, and then placed into a screw machine. The screw machine speed is controlled to be 400 rpm, the temperature is controlled to be 210-270° C., and extrusion granulation is performed to obtain a high-transmittance and low-floating fiber glass fiber reinforced PC composition.

[0067] Example 2

[0068] This embodiment provides a high-transmittance, low-floating fiberglass reinforced PC composition and a preparation method thereof, the method comprising the following steps:

[0069] (1) Preparation of glass fiber grafted with bisphenol A:

[0070] Under nitrogen protection, add 16 g of glass fiber and 4 g of diphenylmethane diisocyanate to 100 ml of anhydrous toluene, act ultrasonically for 30 min, heat and stir at 70 ° C for 2 h, filter and wash three times with anhydrous toluene, and dry at 80 ° C for 4 h to obtain diphenylmethane diisocyanate-modified glass fiber; under nitrogen protection, add 4 g of diphenylmethane diisocyanate-modified glass fiber obtained in the above steps and 4 g of bisphenol A to 100 ml of anhydrous toluene, act ultrasonically for 30 min, heat and stir at 80 ° C for 3 h, filter and wash three times with anhydrous toluene, and dry at 80 ° C for 6 h to obtain modified glass fiber.

[0071] (2) Preparation of modified glass fiber masterbatch:

[0072] 900 g of bisphenol A and 1000 g of the modified glass fiber prepared in step (1) were added to a mixed solvent of 4 L of water and 12 L of dichloromethane. After ultrasonic treatment for 30 min, 450 g of phosgene was introduced at a rate of 30 g / min, and a 50% by mass aqueous solution of sodium hydroxide was slowly added dropwise to control the pH value at 10.5. The mixture was stirred at 30° C. for 1 h. Then, 6 ml of triethylamine was added, the mixture was stirred at 30° C. for 2 h, filtered and washed with water three times, and dried at 90° C. for 8 h to obtain a modified glass fiber masterbatch.

[0073] (3) Prepare the following components by weight:

[0074] PC 60 copies,

[0075] 40 parts of modified glass fiber masterbatch,

[0076] Antioxidant 1010 0.2 parts;

[0077] The ingredients in step (3) are added into a high-speed mixer, mixed thoroughly, and then placed into a screw machine. The screw machine speed is controlled to be 400 rpm, the temperature is controlled to be 210-270° C., and extrusion granulation is performed to obtain a high-transmittance and low-floating fiber glass fiber reinforced PC composition.

[0078] Example 3

[0079] This embodiment provides a high-transmittance, low-floating fiberglass reinforced PC composition and a preparation method thereof, the method comprising the following steps:

[0080] (1) Preparation of glass fiber grafted with bisphenol A:

[0081] Under nitrogen protection, add 16 g of glass fiber and 4 g of diphenylmethane diisocyanate to 100 ml of anhydrous toluene, act ultrasonically for 30 min, heat and stir at 70 ° C for 2 h, filter and wash three times with anhydrous toluene, and dry at 80 ° C for 4 h to obtain diphenylmethane diisocyanate-modified glass fiber; under nitrogen protection, add 4 g of diphenylmethane diisocyanate-modified glass fiber obtained in the above steps and 4 g of bisphenol A to 100 ml of anhydrous toluene, act ultrasonically for 30 min, heat and stir at 80 ° C for 3 h, filter and wash three times with anhydrous toluene, and dry at 80 ° C for 6 h to obtain modified glass fiber.

[0082] (2) Preparation of modified glass fiber masterbatch:

[0083] 900 g of bisphenol A and 1000 g of the modified glass fiber prepared in step (1) were added to a mixed solvent of 4 L of water and 12 L of dichloromethane. After ultrasonic treatment for 30 min, 450 g of phosgene was introduced at a rate of 30 g / min, and a 50% by mass aqueous solution of sodium hydroxide was slowly added dropwise to control the pH value at 10.5. The mixture was stirred at 30° C. for 1 h. Then, 7 ml of triethylamine was added, the mixture was stirred at 30° C. for 2 h, filtered and washed with water three times, and dried at 90° C. for 8 h to obtain a modified glass fiber masterbatch.

[0084] (3) Prepare the following components by weight:

[0085] PC 40 copies,

[0086] 60 parts of modified glass fiber masterbatch,

[0087] Antioxidant 1010 0.2 parts;

[0088] The ingredients in step (3) are added into a high-speed mixer, mixed thoroughly, and then placed into a screw machine. The screw machine speed is controlled to be 400 rpm, the temperature is controlled to be 210-270° C., and extrusion granulation is performed to obtain a high-transmittance and low-floating fiber glass fiber reinforced PC composition.

[0089] Comparative Example 1

[0090] This comparative example provides a glass fiber reinforced PC composition and a preparation method thereof, the method comprising the following steps:

[0091] (1) Prepare the following components by weight:

[0092] PC 80 copies,

[0093] Glass fiber 20 parts,

[0094] Antioxidant 1010 0.2 parts;

[0095] The ingredients in step (1) are added into a high-speed mixer, mixed thoroughly, and then placed into a screw machine. The speed of the screw machine is controlled to be 400 rpm, the temperature is controlled to be 210-270° C., and extrusion granulation is performed to obtain a glass fiber reinforced PC composition.

[0096] Comparative Example 2

[0097] This comparative example provides a glass fiber reinforced PC composition and a preparation method thereof, the method comprising the following steps:

[0098] (1) Prepare the following components by weight:

[0099] PC 70 copies,

[0100] Glass fiber 30 parts,

[0101] Antioxidant 1010 0.2 parts;

[0102] The ingredients in step (1) are added into a high-speed mixer, mixed thoroughly, and then placed into a screw machine. The speed of the screw machine is controlled to be 400 rpm, the temperature is controlled to be 210-270° C., and extrusion granulation is performed to obtain a glass fiber reinforced PC composition.

[0103] Comparative Example 3

[0104] This comparative example provides a high-transmittance, low-floating fiber glass fiber reinforced PC composition and a preparation method thereof, the method comprising the following steps:

[0105] (1) Preparation of glass fiber grafted with bisphenol A:

[0106] Under nitrogen protection, add 16 g of glass fiber and 4 g of diphenylmethane diisocyanate to 100 ml of anhydrous toluene, act ultrasonically for 30 min, heat and stir at 70 ° C for 2 h, filter and wash three times with anhydrous toluene, and dry at 80 ° C for 4 h to obtain diphenylmethane diisocyanate-modified glass fiber; under nitrogen protection, add 4 g of diphenylmethane diisocyanate-modified glass fiber obtained in the above steps and 4 g of bisphenol A to 100 ml of anhydrous toluene, act ultrasonically for 30 min, heat and stir at 80 ° C for 3 h, filter and wash three times with anhydrous toluene, and dry at 80 ° C for 6 h to obtain modified glass fiber.

[0107] (2) Preparation of modified glass fiber masterbatch:

[0108] 900 g of bisphenol A and 1000 g of the modified glass fiber prepared in step (1) were added to a mixed solvent of 4 L of water and 12 L of dichloromethane. After ultrasonic treatment for 30 min, 450 g of phosgene was introduced at a rate of 30 g / min, and a 50% by mass aqueous solution of sodium hydroxide was slowly added dropwise to control the pH value at 10.5. The mixture was stirred at 30° C. for 1 h, filtered and washed with water three times, and dried at 90° C. for 8 h to obtain a modified glass fiber masterbatch.

[0109] (3) Prepare the following components by weight:

[0110] PC 40 copies,

[0111] 60 parts of modified glass fiber masterbatch,

[0112] Antioxidant 1010 0.2 parts;

[0113] The ingredients in step (3) are added into a high-speed mixer, mixed thoroughly, and then placed into a screw machine. The speed of the screw machine is controlled to be 400 rpm, the temperature is controlled to be 210-270° C., and extrusion granulation is performed to obtain a glass fiber reinforced PC composition.

[0114] Test Case

[0115] After melt extrusion granulation in the above embodiments and comparative examples, ASTM standard test specimens were injection molded on an injection molding machine. The test conditions were all carried out in accordance with the ASTM standard system. The materials obtained in embodiments 1-3 and comparative examples 1-2 were subjected to performance tests, and the test results are shown in Table 1.

[0116] Table 1 Test performance results

[0117]

[0118]

[0119] From the comparative analysis of the test results of Examples 1 to 3 and Comparative Examples 1 to 2, it can be seen that the preparation method of first obtaining a modified glass fiber masterbatch grafted with a PC molecular chain and then mixing and processing PC, the modified glass fiber masterbatch and the antioxidant in the examples, the glass fiber prepared by this method has good compatibility with PC, good dispersion in PC, can improve the transparency of the product, and has good material performance. From the comparative analysis of the test results of Example 3 and Comparative Example 3, it can be seen that the modified glass fiber obtained by adding triethylamine in the examples has better compatibility with PC, and the transparency and performance of the material are better.

[0120] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A glass fiber reinforced PC composition, characterized in that: The composition comprises the following components in parts by weight: 40-70 parts of PC resin, 30-60 parts of glass fiber masterbatch, and 0.1-1 part of antioxidant; the glass fiber masterbatch is prepared by adding aromatic dihydroxy compound to modify glass fiber during PC polymerization, and specifically comprises the following steps: S1. Preparation of modified glass fiber: S1-1, under nitrogen protection, adding glass fiber and diphenylmethane diisocyanate to anhydrous toluene, ultrasonicating for 10-30 min, heating and stirring at 70-90 ° C for 0.5-4 h, filtering and washing with anhydrous toluene, and drying at 40-80 ° C to obtain diphenylmethane diisocyanate modified glass fiber; the amount of glass fiber added is such that the mass ratio of glass fiber to diphenylmethane diisocyanate is 1:0.1-0.5; S1-2, under nitrogen protection, adding the diphenylmethane diisocyanate modified glass fiber and the aromatic dihydroxy compound into anhydrous toluene, ultrasonicating for 10-30 min, heating and stirring at 60-80 ° C for 2-6 h, filtering and washing with anhydrous toluene, and drying at 40-80 ° C to obtain modified glass fiber; the amount of the aromatic dihydroxy compound added is such that the mass ratio of the aromatic dihydroxy compound to the diphenylmethane diisocyanate modified glass fiber is 1:0.5-1; S2. Preparation of modified glass fiber masterbatch: Add an aromatic dihydroxy compound and the modified glass fiber to a mixed solvent of water and dichloromethane, subject the mixture to ultrasonic treatment for 10-30 min, introduce phosgene at a rate of 15-30 g / min, and slowly drop a 30-50% mass fraction sodium hydroxide aqueous solution to control the pH value between 8 and 11, and stir at 10-40 ° C for 1-3 h; then add triethylamine, stir at 10-40 ° C for 1-3 h, filter and wash with water, and dry at 70-90 ° C to obtain a modified glass fiber masterbatch; The amount of the modified glass fiber added is such that the mass ratio of the modified glass fiber to the aromatic dihydroxy compound is 1:0.5-4; the amount of phosgene added is 100-120 g per 1 mol of the aromatic dihydroxy compound; and the amount of triethylamine added is 1-2 ml per 1 mol of the aromatic dihydroxy compound.

2. The glass fiber reinforced PC composition according to claim 1, characterized in that: The PC resin is a linear homopolymer polycarbonate of bisphenol A, and has a melting index of 10 to 30 g / 10 min at 300° C. and 1.2 kg.

3. The glass fiber reinforced PC composition according to claim 1, characterized in that: The glass fiber has a diameter of 5-20 μm, a length of 1-5 mm, and a refractive index of 1.

57.

4. The glass fiber reinforced PC composition according to claim 1, characterized in that: The antioxidant is selected from one or more of aromatic amine antioxidants, hindered phenol antioxidants, phosphite antioxidants, thioester antioxidants, aromatic phosphates, and pentaerythritol esters.

5. The glass fiber reinforced PC composition according to claim 1, characterized in that: In step S1-1, the amount of diphenylmethane diisocyanate added is 1-5 g per 100 ml of anhydrous toluene.

6. The glass fiber reinforced PC composition according to claim 1, characterized in that: In step S1-2, the amount of diphenylmethane diisocyanate modified glass fiber added is 1-5 g per 100 ml of anhydrous toluene.

7. The glass fiber reinforced PC composition according to claim 1, characterized in that: In step S2, the volume ratio of water to dichloromethane in the mixed solvent is 1:2-4; the amount of the aromatic dihydroxy compound added is 5-25 g per 100 ml of water.

8. A method for preparing a glass fiber reinforced PC composition according to claim 1, characterized in that: The method comprises the following steps: 40-70 parts of PC, 30-60 parts of modified glass fiber masterbatch and 0.1-1 part of antioxidant are mixed at high speed and placed in a screw machine, the speed of the screw machine is controlled to be 300-500 rpm, the temperature is controlled to be 200-270° C., and extrusion granulation is performed to obtain the glass fiber reinforced PC composition.